IMPLEMENTASI METODE DRILL DALAM MATA PELAJARAN AL-QUR’AN HADITS KELAS VA DI MI NU MAUDLU’UL ULUM KOTA MALANG - Fitriani Sundari; Devi Wahyu Ertanti; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is about the teacher’s afforts in coveying learning material with the right method, because there are student who have not mastered the subject and shows the lack of student participation in learning in MI NU Maudlu’ul Ulum. This sudy use a qualitative method with the type of case study research, where the document based on note of observations, interview and documantation, and analyzed lesson plan by teacher. This research, the implementation of the drill method in learning the Qur'an hadith class va surah al-Qadr material teachers provide exercises to students in the form of reading, translating, writing, memorizing, & discussing so that in addition to individual activities there are also group activities so that students not easily bored during lessons. The obstacle to applying the method is that the focus of the student is not as optimal as his peers who read while paying attention to the surah in the book. While the supporting factor in the implementation of the drill method is that most students in the class can already read the quran. The solution to the problem above is the teacher asking students to read in pairs then alternating with each other.Key word: drill methode, al-qur’an hadits learning